(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Rheumatoid arthritis is a sign of progressive degradation of cartilage, subchondral bone, and small joints, as well as the persistence of synovitis and the formation of pannus. This research intends to assess the purported anti-arthritic effects of an extract from the seeds of Portulaca oleracea. Female Wistar albino rats (140–200 g) were used and assigned to five groups: Group I administrated NS (10 ml/kg), Group II received 0.2 ml of CoII-IFA, Group III received 300 mg/kg of fish oil, and Groups IV & V administrated 100 and 200 mg/kg of methanolic extract of Portulaca oleracea (MePO). During the experiment, the rats' weight, arthritic score, and footpad oedema were evaluated to determine the severity of their arthritis. Later, blood samples were collected from the animals, which were then analysed for haematological, pro-inflammatory, antioxidant, and histological parameters. A dose-dependent reduction was seen in rats treated with a methanolic extract of Portulaca seeds. Levels of haematological and pro-inflammatory cytokines were considerably reduced by treatment. Although both the standard drug and 200 mg/kg of MePO had anti-inflammatory effects, the latter's were more pronounced at this dose. When looking at the two side by side, results showed that the treatment groups of RBC, WBC, NL-ratio, and ML-ratio levels were normalised. Further histology confirmed the reduction of joint deformity, oedema, formation of pannus, and infiltration of neutrophils in the MePO groups in contrast to arthritic rats. It is hypothesised that Portulaca oleracea may reduce the arthritis and can be used as an adjuvant therapy or incorporate it into your diet with the main course of treatment.